Pengaruh Jumlah Plat Helical Terhadap Daya Dukung Pondasi Tiang Helical Pada Tanah Gambut - Parlan, Parlan; Fatnanta, Ferry; Muhardi, Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Helical Pile A manufactured steel foundation consisting of one or more helix-shaped bearing plates affixed to a central shaft that is rotated into the ground to support structures. At thisresearch will be presented result of static loading test constan rate penetration method (CRP) helical pile conducted at peat. Result of data from loading test in the form of load and degradation interpretation with tangen of intersection method. addition sum up the same plate helical diameterwill improve the capacities support helical pile. But if plate helical most under smaller hence addition sum up the plate helical do not have an effect on the signifikan to Qultimate the helicalpile though plate helical for bigger. Result of the encumbering attempt compared to by result of energy calculation support the helical pile use the method of Induvidual plate bearing and cylindershear. From comparison result known that by Qultimate the method of cylinder shear more coming near result of burden test with the standard error 2,37 while ,Qultimate the individual method of plate bearing come near result of burden test with the standard error 4,38.Key words : helical pile, peat, individual plate bearing, cylinder shear